The Effect of Compaction Pressure of Evaporation Boats, Kaolin and Rice Husk Charcoal Composition on Thermal Conductivity and Microstructure - Casminto; Rusiyanto; Sunyoto; Kriswanto (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
Evaporation boats waste is a waste that is difficult to decompose which has characteristics as a material for makingowi, but its utilisation is still not optimal. The purpose of this study was to determine the effect of compaction pressure on the thermal conductivity and microstructure of aowi made from evaporation boats, kaolin and rice husk charcoal. The research method used was experimental. The independent variable used in this study is the kowi compaction pressure with variations of 20 MPa, 25 MPa, 30 MPa, 35 MPa. The composition of the materials used is 50% evaporation boats, 35% kaolin powder, and 15% rice husk charcoal and 15% water from the total weight of the materials in the mixing. The dependent variables in this study are thermal conductivity testing and microstructure observation. Control variables in this study are powder particle size 100 mesh, mixing time 90 minutes, thickness 2 and 4 mm, specimen diameter 40 mm, firing temperature used 8000C, and holding time 2 hours. The results showed that the average value of the highest thermal conductivity of 4.1045 W / MK at a compression pressure of 35 MPa and the lowest thermal conductivity value of 3.3499 W / MK at a compression pressure of 20 MPa. The higher the compression pressure, the greater the value of thermal conductivity. This is because the greater the compression pressure, the stronger the bond between particles and pores are reduced so that the density increases. The microstructure shows a difference in phase at each compression pressure given. The greater the compression pressure applied, the tighter the density of the material. Keywords: Compression Pressure, kowi, evaporation boats, kaolin, rice husk charcoal, thermal conductivity, microstructure